2020
DOI: 10.32892/jmri.233
|View full text |Cite
|
Sign up to set email alerts
|

Health care professional knowledge and attitude towards the use of digital technologies in provision of maternal health services at Tumbi regional referral hospital in Tanzania

Abstract: Objectives: In recent years Tanzania introduced digital technologies in health industry where several initiatives such as Government of Tanzania, Hospital Management Information System (GoT-HoMIS) along other digital devices are taken to ensure quality services delivery. The purpose of this study was to assess Health Care Providers (HCPs) knowledge and attitude towards the use of Digital Health Technology (DHT) in provision of maternal health services at Tumbi Regional Referral Hospital (TRRH). Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…The bundles led to positive experiences among health workers regarding service provision, which is not surprising. One previous study conducted about health workers' knowledge and attitudes towards the use of digital technologies in the provision of maternal health services at Tumbi Regional Referral Hospital in Tanzania found increased use of digital health technologies [30]. The study further showed that health workers understood the importance of digital health technologies in improving maternal health services besides reporting a positive attitude towards digital health technologies [30].…”
Section: Plos Onementioning
confidence: 65%
See 1 more Smart Citation
“…The bundles led to positive experiences among health workers regarding service provision, which is not surprising. One previous study conducted about health workers' knowledge and attitudes towards the use of digital technologies in the provision of maternal health services at Tumbi Regional Referral Hospital in Tanzania found increased use of digital health technologies [30]. The study further showed that health workers understood the importance of digital health technologies in improving maternal health services besides reporting a positive attitude towards digital health technologies [30].…”
Section: Plos Onementioning
confidence: 65%
“…One previous study conducted about health workers' knowledge and attitudes towards the use of digital technologies in the provision of maternal health services at Tumbi Regional Referral Hospital in Tanzania found increased use of digital health technologies [30]. The study further showed that health workers understood the importance of digital health technologies in improving maternal health services besides reporting a positive attitude towards digital health technologies [30]. In another Tanzanian study, a mobile job aid was successfully used to support the counseling of women about contraception [31], which is consistent with our findings about the better quality of care during the postnatal care period due to the bundles.…”
Section: Plos Onementioning
confidence: 95%
“…Tis method also seeks to activate generalizable statements to use them to provide advice and guidance to practitioners and policymakers [24,25]. According to scientifc innovations, the world emphasizes improving maternal health services using digital technologies [46]. Tis review presented studies from six virtual approaches of mHealth, eHealth, telehealth, remote care, virtual visits, and applications for prenatal care.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of supportive health infrastructure, locally located servers and poor network availability: The founder pointed out that, most health facilities, especially public health facilities, do not have digital systems/hardware that we can leverage for AI technology. Either they do not have any technology at all and are relying on paper-based systems, or they have an electronic health records system which utilizes the Government of Tanzania Health Operations Management Information System (GOT-HOMIS) (Thadeus Kissima and Mushi, 2021 ) or AfyaCare 9 government systems. These are very difficult to integrate with Dr. Elsa's zool.…”
Section: Case Studies Of Ai Adoption In Anglophone Africamentioning
confidence: 99%